2010
DOI: 10.1111/j.1600-0625.2009.00981.x
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB is involved in inhibition of lipoxin A4 on dermal inflammation and hyperplasia induced by mezerein

Abstract: Abstract:The mechanisms by which lipoxin A 4 (LXA 4 ) inhibit skin inflammation remain unclear. In the present studies, the ear inflammatory model was induced by topical application of mezerein. Treatment of the mouse ear with LXA 4 exhibited the inhibitory effects on oedema, neutrophil infiltration, vascular permeability, expressions of interleukin (IL)-1, IL-6 and IL-8 mRNA, DNA-binding activity of nuclear factor-jB (NF-jB), and on dermal hyperplasia. NF-jB reporter activities and nuclear translocations of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…The degradation of IκBα and nuclear translocation of p65 induced by IL-1β were also dramatically blocked by pretreatment of the cells with TLR2Ab, ST2825 and TPCA-1. LXA4 and its analog inhibited degradation, but not phosphorylation of IκBα in epithelial cells and keratinocytes ( 25 , 26 ), and in analogy with this, the present study detected degradation of IκBα but not phosphorylation of IκBα.…”
Section: Resultssupporting
confidence: 89%
“…The degradation of IκBα and nuclear translocation of p65 induced by IL-1β were also dramatically blocked by pretreatment of the cells with TLR2Ab, ST2825 and TPCA-1. LXA4 and its analog inhibited degradation, but not phosphorylation of IκBα in epithelial cells and keratinocytes ( 25 , 26 ), and in analogy with this, the present study detected degradation of IκBα but not phosphorylation of IκBα.…”
Section: Resultssupporting
confidence: 89%
“…Topical efficacy for native LXA 4 and its analogs has been demonstrated in several models of skin inflammation, 3–5 and in models of keratitis and uveitis 6,7 . Our investigations, and those of others, have also demonstrated that LXA 4 is a potential anti‐inflammatory and antihyperplasia drug targeting the skin 8,9 . Although the studies performed by Christie et al.…”
supporting
confidence: 66%
“…The mechanisms by which 15(R/S)‐methyl‐LXA 4 inhibited the inflammatory reaction of eczema were not explored in the current study. Our previous results demonstrated that treatment of mouse ear with LXA 4 exhibited the inhibitory effects on skin oedema, neutrophil infiltration, vascular permeability, expressions of IL‐1, IL‐6 and IL‐8, and on dermal hyperplasia induced by mezerein 8 . Chen et al.…”
Section: Discussionmentioning
confidence: 94%
“…LXA 4 exhibited inhibitory effects on edema, neutrophil infiltration, and vascular permeability, expressions of interleukin (IL)-1, IL-6, and IL-8 mRNA, DNA-binding activity of nuclear factor-kappaB (NF-kappaB), and blocked NF-kappaB reporter activities and nuclear translocations of NF-kappaB p65. Thus, LXA 4 showed potent anti-inflammatory and anti-proliferative action by downregulating DNA-binding activity of NF-kappaB (42) and NF-κB, in turn when upregulated blocks LXA 4 formation [148]. In view of their anti-inflammatory action and since cancer cell growth and invasion could be considered as an inflammatory event, it is expected that anti-inflammatory compound LXA 4 will have anti-proliferative and antiinvasive (and thus suppress metastasis) properties.…”
Section: Differential Action Of Pufas On Normal and Tumor Cellsmentioning
confidence: 99%